Review of Microleon Butler, 1885 (Lepidoptera: Limacodidae) from Taiwan with description of a new species based on morphology and DNA barcoding - Sohn, Jae-Cheon; Shih, Li-Cheng; Wu, Shipher (Zootaxa, 2024)
The Taiwanese species of Microleon are reviewed with morphological and DNA data. Our review recognized two congeners, including a new species, M. taiwanensis n. sp. and one known species, M. longipalpis Butler, 1885. The findings from this study request a reconsideration of the previous records of Microleon from Taiwan. The minor differences in external appearance among the species of Microleon pose a challenge for reliable identification. Our study shows that examination of the male genitalia and COI barcoding helps distinguish the species. A checklist of the world species of Microleon with their distributional range is provided.